Zarządzanie ryzykiem społecznym w ubezpieczeniach emerytalnych - Nagel, Wojciech (Management of social risks in capital-based pension schemes, 2006)
The current year completes the six-year period of functioning of the new capital based pension system in Poland. In the foundation of this new system was the idea of sharing of responsibility for the future pension benefits between employers and employees. The pension system reform, however delayed, was certainly indispensable, but the evaluation as to whether its assumptions has been accomplished is not an easy undertaking nowadays. The creation on a wides cale pension insurance schemes in companies was not achieved. In Europe, company pension plans are well developed and, in numerous occasions, are an example of a good cooperation between employees and employers. Several malfunctions were also present in the operations of open pension funds, which have not been receiving money transfers (as required by law). Many people even up till now have not received part of their pension contributions, transferred through Social Insurance Institution (ZUS) to open pension funds by their employers. This paper attempts to characterize, from the domestic perspective, the social risks present in the field of capital based pension schemes. This subject is relatively rarely elaborated, but important due to possibility of emergence of some adverse social effects in the following decades. The possible emergence of these adverse effects can be found in demographical forecasts and long term economical and work market indicators.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 351-358